Critical success factors: the success of business intelligence systems. (2017) - Rajesh, K.; Saravanan, D.
Business intelligence (BI) systems have the potential to improve business performance by facilitating innovations, creating new products and service, and enhancing decision making effectiveness. However, it requires certain institutional and scientific capabilities to fully realise the values of BI systems. One of the critical issues concerned with BI systems (BIS) for both researchers and practitioners is to identify the factors which are very important for successful implementation of business intelligence projects. Hence, this paper provides a brief explanation about the most general and impact factors which can be impacting in implementing business intelligence projects in organisations. I anticipated that it is critical to determine these factors, particularly for practitioners of those companies are involved in carry out business intelligence projects and they face a problem in evaluating the willingness of their organisations before implementing the project in pre-implementation stage. The objective of this paper is to provide a better understanding of the vital and valuable success factors and it is to conduct a survey and comprehensive study of the critical success factors before implementation phase of the willingness by categorising the factors into two main groups; institutional and scientific factors. It is clear that each category has its own features and a brief explanation of each factor is discussed.